2019
DOI: 10.1080/15228835.2019.1584598
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Surveillance in Social Work: Practice Realities and Ethical Implications

Abstract: This article reports on findings from a study with recently qualified social workers on the use of social media in their practice. The findings reported here are drawn from a broader study on the use of electronic communications conducted with both newly qualified teachers and social workers. The focus group data reported here provide an insight into the practice realities associated with the use of social media by clients and social workers. The qualitative methodology employed helps to reveal the richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Power differences between CWWs and their clients are recognized in the literature on technology and child welfare (Byrne et al, 2019) and are evident in the study reported here. For example, sometimes CWWs use social media to surveil the posts of clients and their families for information about their whereabouts or activities.…”
Section: Discussionsupporting
confidence: 56%
“…Power differences between CWWs and their clients are recognized in the literature on technology and child welfare (Byrne et al, 2019) and are evident in the study reported here. For example, sometimes CWWs use social media to surveil the posts of clients and their families for information about their whereabouts or activities.…”
Section: Discussionsupporting
confidence: 56%
“…The ethical principles of research require that the right to privacy of research participants be respected in the course of the data-collection process and thereafter (Creswell, 2017). Also, obtaining consent from individual participants through WhatsApp proved daunting during the pandemic (and even before) (Byrne et al, 2019). As stated by Hensen et al (2020), in some instances a research participant may be under the age of 18 and then consent is required from a parent or guardian, or it might be a challenge to authenticate the former’s age.…”
Section: Resultsmentioning
confidence: 99%
“…Admittedly, some participants used emojis, which facilitated interpretation. Another limitation was the lack of rich literature on using WhatsApp as a data-collection method (Byrne et al, 2019). The pandemic has created an opportune scenario for scholars to explore the possibilities of using various social media platforms as data-collection instruments, to overcome the increasing challenges and complexities of social science research in this day and age (Barbosa & Milan, 2019; Cetinkaya, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Sarah Brayne ( 2014 ) finds that government surveillance via social media and other means encourages marginalized communities to engage in “system avoidance,” jeopardizing their access to valuable social services in the process. Finally, people accustomed to being surveilled will not hesitate to instrumentalize social media to reverse monitor their relationships with surveilling institutions, for instance by taping public interactions with police officers or with social workers and sharing them online (Byrne et al 2019 ). While this kind of resistance might further draw a wedge between vulnerable populations and those formally in charge of assisting and protecting them, it has also become a powerful aspect of grassroots mobilization in and around machine learning and techno-social approaches to institutional reform (Benjamin 2019 ).…”
Section: Ordering Social and Automatedmentioning
confidence: 99%